Vereinfachtes Modell zur Abschätzung der Arbeitsweise einer Wirbelschicht mit Eigenkeimbildung bei Flüssigkeitseindüsung. Issue 8 (9th July 2018) - Mörl, Lothar; Idakiev, Vesselin V.; Schönherr, Michael; Jacob, Michael
Abstract: For the production of particles in fluidized beds with a monodisperse grain band spectrum usually sift‐grind cycles are used. The agglomeration phenomena occurring in this process, the disintegration, the abrasion, the overspray and the dust binding, are usually not considered individually. The aim of this research work is to determine the dependence of specific process parameters on a special fluidized bed granulation process with self‐nucleation in order to make it more controllable. For a more detailed description of this process, a simplified mathematical model is presented in this paper.